Reverse Mechanism Selection Sebagai Instrumen Rekonfigurasi Seleksi Penyelenggara Pemilihan Umum: Menata Ulang Keterlibatan Dewan Perwakilan Rakyat Untuk Menjamin Kemandirian - Nugraha, Dwi Putra; Silalahi, Jordan Baros Indraputra; Silalahi, Thomas Rifera Indraputra (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The selection process for members of the General Elections Commission (KPU) and the Election Supervisory Body (Bawaslu) in Indonesia plays a strategic role in ensuring the integrity of electoral democracy. Although designed based on the principle of checks and balances, the dominance of the House of Representatives (DPR) in the final stages of the selection process opens up room for political intervention that threatens the independence of the election organisers. This article aims to examine the effectiveness of the current selection design and propose an alternative conceptual model in the form of a reverse mechanism selection, a reversal of the selection authority structure as an instrument for reconstructing a more independent selection governance system. The research method used is normative legal research, with a statutory approach and a comparative analysis of the selection mechanism for election organisers. The results indicate that the final authority held by the DPR without an independent oversight mechanism reduces institutional independence and increases the potential for politicization. Therefore, this article recommends a reconfiguration of authority through a reverse mechanism selection model, in which an independent Selection Team holds final decision-making authority, while the DPR is limited to nominative and administrative functions. This concept provides a conceptual contribution to strengthening the principle of independency of the election organisers and encourages legal reform to increase accountability and neutrality in the selection process.